2020
DOI: 10.1097/dbp.0000000000000852
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Criteria for Eligibility Determination for Early Intervention Services with a Focus on Eligibility for Children with Neonatal Complications

Abstract: Objective: The purpose of this policy review is to describe data on eligibility determination practices for early intervention (EI) services across the United States as they particularly relate to eligibility determination for children seen in neonatal follow-up clinics. Method: Policy information was gathered from posted information on state EI websites and confirmed through follow-up phone calls. Information collected included definition of delay, app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The least common methods for determining eligibility were MTSS/RTI and a discrepancy model. EI eligibility was more likely to use a percentage delay and clinical judgment, aligning with prior research that has also found that percent delay was commonly used for determining EI eligibility (Dempsey et al, 2020). Although federal IDEA (2004) policies are meant to be interpreted and further defined at the state-level, the present results suggest that location in a particular state still holds a large influence on whether a child is eligible for EI or preschool special education.…”
Section: Determining Eligibilitysupporting
confidence: 85%
See 1 more Smart Citation
“…The least common methods for determining eligibility were MTSS/RTI and a discrepancy model. EI eligibility was more likely to use a percentage delay and clinical judgment, aligning with prior research that has also found that percent delay was commonly used for determining EI eligibility (Dempsey et al, 2020). Although federal IDEA (2004) policies are meant to be interpreted and further defined at the state-level, the present results suggest that location in a particular state still holds a large influence on whether a child is eligible for EI or preschool special education.…”
Section: Determining Eligibilitysupporting
confidence: 85%
“…Participants suggested that their state’s guidance regarding approved assessment tools influenced their choice of assessments to use during the initial evaluation. Recent findings revealed that there are 19 suggested or approved assessments in 39 US states (Dempsey et al, 2020 ). Interestingly, respondents in the present study reported the use of a wider range of tools than in prior research, which might be due to the present study including evaluations for both EI and preschool special education.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the number of responses from each state was highly variable. Given that state-level policy is highly influential in assessment and eligibility practices (Dempsey et al, 2020), this likely impacted our findings and may not represent this work across all U.S. states. Second, the respondents primarily identified as White and female.…”
Section: Discussionmentioning
confidence: 99%
“…If the PN were unable to reach a family, she would contact the local EI office to determine if the child had been evaluated and/or found eligible for services. At the time of this study, eligibility for EI in our state was determined by a 33% delay in one or more developmental areas, or a combination of biomedical risk factors (Dempsey et al, 2020).…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Part C of the Individuals with Disabilities Education Act (IDEA) provides states with funding to offer early intervention (EI) services to children who have or are at risk for DD "to enhance the development of infants and toddlers with disabilities, to minimize their potential for DD and to recognize the significant brain development that occurs during a child's first 3 years of life" (Office of the Federal Register, National Archives and Records Administration, 2004). Although all 50 states have EI programs as mandated by IDEA, each state determines the degree of delay a child must demonstrate to qualify for EI, which results in a substantial variation across states (Dempsey et al, 2020). EI has the potential to improve developmental outcomes and decrease the need for future intervention (Dawson et al, 2010(Dawson et al, , 2012Howlin et al, 2009;McCormick et al, 2006;Walker et al, 2011).…”
mentioning
confidence: 99%